THE ROLE OF NGOS IN GIVING ASSISTANCE FOR EXTERNALAND INTERNAL REFUGEES AS A BOUNDARY VIOLATION OF A SOVEREIGN STATE - Marliana, Marliana (Indonesian Journal of International Law, 2013)
An NGO (Non-Governmental Organization) is a legally constituted organization created by natural or legal persons that operates independently from any form of government, thus is a humanity-value-based organization that provides assistance in a form of charities and voluntary services. These kinds of assistance are much-needed relief for refugees in the countries of armed conflict or not. The most important source of protection for external refugees is Refugees Law while the internal refugees are protected by the National Law. The study presented in this paper is limited to assistance provided by NGOs to external and internal refugees in a country that is not in situations of armed conflict. These limits are given to address whether the role of NGOs providing assistance to refugees can be categorized as a violation of the limit state sovereignty. This level of understanding in the area of theoretical but can be implemented to legitimate the role of NGOs.